2020
DOI: 10.3390/ijerph17061836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Survival and the Cold-Induced Gene Expression of Pathogenic and Nonpathogenic Vibrio Parahaemolyticus from Tropical Eastern Oysters during Cold Storage

Abstract: Expression of the regulatory stress rpoS gene controls the transcription of cspA genes, which are involved in survival and adaptation to low temperatures. The purpose of this study was to assess the growth kinetics of naturally occurring V. parahaemolyticus in shellstock oysters and in vitro and the cold-shock-induced expression of the rpoS and cspA gene response in vitro during postharvest refrigeration. Naturally contaminated eastern oysters (Crassostrea virginica) and pathogenic (Vp-tdh) and nonpathogenic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that V. parahaemolyticus isolates that do not have the tdh and/or trh genes also exhibit significant cytotoxicity towards human gastrointestinal cells, suggesting the presence of alternative virulence-associated genes [ 61 ]. In this study, several putative genes related to virulence ( n = 43–45) were identified in the three V. parahaemolyticus genomes ( Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that V. parahaemolyticus isolates that do not have the tdh and/or trh genes also exhibit significant cytotoxicity towards human gastrointestinal cells, suggesting the presence of alternative virulence-associated genes [ 61 ]. In this study, several putative genes related to virulence ( n = 43–45) were identified in the three V. parahaemolyticus genomes ( Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Growth rates of pathogenic Vibrio strains ( tdh -positive) may be higher than growth rates of confirmed V. parahaemolyticus ( tlh -positive), and therefore we may be underestimating tlh -positive cells due to the high incubation temperature ( Alarcón Elvira et al, 2020 ). However, in this study, the incubation temperature to enumerate culturable Vibrio was chosen to select for human pathogens that would optimally grow at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…For example, maximum V. parahaemolyticus densities were higher in Eastern oysters stored at 20–25 °C [ 22 ] and PO injected with V. parahaemolyticus , but lower in natural POs and SROs [ 19 ] compared to BROs (current study). The maximum population densities for V. parahaemolyticus or any pathogen may depend on the type and density of other resident microbiota [ 43 , 44 ] including non-pathogenic environmental Vibrio species that may inhibit pathogenic Vibrio species [ 45 , 46 ]. Work is currently underway to measure the whole microbial community (total bacteria and Vibrio species) in stored BROs from this study to assess the impact of inoculated V. parahaemolyticus on the resident oyster microbiome compared to the seawater inoculated controls.…”
Section: Discussionmentioning
confidence: 99%